Pemanfaatan Teknologi dan Komunikasi dalam Penerapan Flexible Working Arrangement (FWA) Badan Pusat Stastik Provinsi Jawa Barat - Hariani, Marisa; Wahyudin, Uud; Gemiharto, Ilham (REFORMASI, 2025)
The West Java Provincial BPS (Statistics Indonesia) is one of the work units conducting a pilot test for the expansion of Flexible Work Arrangements (FWA) at Statistics Indonesia. BPS has adopted the FWA system to support employee productivity and work-life balance. This study aims to examine the utilization of computer-mediated communication (CMC) technology in the implementation of FWA at the West Java Provincial BPS. The research uses a qualitative descriptive approach with analysis based on Elton Mayo's Human Relations Theory. Data was collected through interviews, observations, documentation, and literature review. Data analysis was carried out through the processes of data collection, reduction, presentation, and conclusion drawing. Data validity was ensured using source triangulation. The results show that the use of technology in the implementation of FWA at the West Java Provincial BPS involves CMC technology. Vertical and formal communication is often conducted through online meetings using applications such as Zoom or Google Meet, as well as via chat, voice, or video calls on WhatsApp. Collaborative platforms like Google Sheets and web-based application development are also utilized. Informal vertical, horizontal, and diagonal communication is more frequently used by team leaders and team members during FWA as it is faster and provides more spontaneous responses. Managing the balance between formal and informal communication is crucial in FWA, particularly in maintaining productive and cohesive team relationships.BPS Provinsi Jawa Barat merupakan salah satu satuan kerja yang melaksanakan uji coba perluasan FWA Badan Pusat Statistik. BPS mengadopsi sistem FWA untuk mendukung produktivitas pegawai dan keseimbangan antara kerja dan kehidupan pribadi. Penelitian ini bertujuan untuk mengetahui pemanfaatan teknologi komunikasi yang dimediasi computer (CMC) dalam pelaksanaan penerapan FWA di BPS Provinsi Jawa Barat. Penelitian menggunakan pendekatan deskriptif kualitatif dengan analisis menggunakan Teori Hubungan Manusiawi dari Elton Mayo. Pengumpulan data dilakukan melalui wawancara, observasi, dokumentasi, serta kajian pustaka. Teknik analisis data dilakukan melalui proses pengumpulan, reduksi, penyajian data dan penarikan Kesimpulan. Validitas data menggunakan teknik triangulasi sumber. Hasil penelitian menunjukkan pemanfaatan teknologi dalam pelaksanaan FWA di BPS Provinsi Jawa Barat menggunakan teknologi CMC. Komunikasi vertikal dan formal sering dilakukan melalui rapat online menggunakan aplikasi Zoom atau Google Meet. Percakapan via chat, voice atau video call Whatsapp. Platform kolaborasi seperti google sheet dan pembanguna aplikasi berbasis web. Komunikasi vertikal, horizontal dan diagonal secara informal lebih sering digunakan ketua tim dan anggota tim saat FWA karena lebih cepat dan memberikan respon yang lebih spontan. Mengelola keseimbangan antara komunikasi formal dan informal menjadi sangat penting dalam FWA, terutama untuk menjaga agar hubungan sosial tim tetap produktif dan kohesif.